Results of Treatment of Hydrocephalus in Tembakau Deli Hospital, Medan, Indonesia - Ahmad Dian Siregar; Z. Siregar; M. Sjabaroeddin Lubis; H. Siregar (Paediatrica Indonesiana, 1997)
There were 9 eases of hydrocephalus that we followed up and reported in this paper. The youngest case was 3 'months. The type of hydrocephalus were: 5 cases with acquired, 2 cases with congenital and remaining cases with neoplastic hydrocephalus. Three pallets were treated medically and the others were using VP-shunt. Five patients using VP-shunt hawe functioning failure so that in three of them the shunt had to be removed and the others had to be combined with medical treatment. Only one patient revealed a benefit of shunting with clinical improvement. Two cases that VP-shunt had removed and continued with medical treatment. Three patients who were treated only by medical treatment showed good improvement. Because of the expensive for using VP-shunt and some evidence of its failure in most of our cases, we preferred to put medical treatment in the forefront before considered shunting in patients with hydrocephalus.